Strategi Peningkatan Kinerja Keuangan Perbankan Syariah Setelah Pandemi Covid-19 - Dwi Kharismawati (Jurnal Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
The purpose of this study is to find out about the strategies used by Islamic Banking in Indonesia to remain competitive in the post covid-19 pandemic. The method used in this study is a literature review and observation of phenomena that are happening at this time. The method used in this research is descriptive qualitative analysis. The results of observations made by looking at financial performance data at the OJK in 2020-2022 state that there has been and increase in revenue (total asset) from year to year after the covid-19 pandemic. The strategy that has been implemented by Islamic banking in improving financial performance after the covid-19 pandemic is issuing various regulations that accelerate digital transformation and synergy in the banking sector. In addition to digital transformation, Islamic banks are required to innovate as a strategy to improve financial performance